A Critical Analysis Of The Implementation Of The Job Creation Law In Indonesia's Labor Sector - Makhfud, Amirul; Is’aad, Hanifah; Khoirunnisa, Nisrina (Malaqbi Publisher, 2024)
The implementation of the Job Creation Law has sparked debates in Indonesia's labor sector. Aiming to enhance work flexibility and investment competitiveness, this regulation alters various aspects of worker protection. However, these changes are perceived as compromising workers' rights and creating job insecurity. This study examines the implications of the UU Cipta Kerja on workers' rights protection and its alignment with social justice principles. Using a normative juridical method with statutory and case approaches, the research identifies the social and economic impacts of the law's implementation. The findings indicate that, while benefiting employers through flexibility and investment attractiveness, the law poses serious challenges, including potential labor exploitation and instability in industrial relations. This study recommends reforming public participation in policymaking and strengthening regulatory enforcement to ensure better protection of workers' rights.